Mathematics and computing : third International Conference, ICMC 2017, Haldia, India, January 17-21, 2017, Proceedings /: third International Conference, ICMC 2017, Haldia, India, January 17-21, 2017, Proceedings. (2017) - Unknown
No abstract available